Effectiveness of Pelican Crossing on Traffic Flow (Case Study: M.H. Thamrin Road and Sudirman Road, Central Jakarta City) - Simanjuntak, Windy Aprilia; Soehodho, Sutanto; Sumabrata, Jachrizal (Eduvest - Journal of Universal Studies, 2023)
Pelican Crossing is a crossing with a signaling device that is operated by pedestrians and will stop the flow of vehicle traffic. Pedestrians must press a button to request green time from vehicle drivers so that vehicle drivers stop and pedestrians can cross the road. As a metropolitan city, Central Jakarta is full of activity. The increase in the number of vehicles is not the main factor causing congestion. There are other factors such as the movement of pedestrians crossing the road using Pelican Crossing, causing queues and delays. This study aims to analyze the effect of pedestrians crossing at pelican crossing on the queue length of vehicles, to analyze the characteristics of traffic flow and pedestrians due to pelican crossing and to apply a model that connects the characteristics of traffic flow and pedestrians at pelican crossing. The research was conducted by surveying the existing traffic conditions. The results of the research show that after calculating the PV2 value, we can see the discrepancy in the existing pelican crossing facilities on Jalan MH Thamrin and Jalan Sudirman based on the calculation of pedestrian crossings and traffic volume, which in calculating the PV2 value recommends a non-level crossing type.